Pentinya Penyuluhan Pernikahan Dini Sebagai Upaya Menghentikan Pertumbuhan Angka Janda di Lombok - sukardiman, sukardiman (Institut Agama Islam Negeri Padangsidimpuan, 2022)
AbstracEarly marriage is indeed a frightening specter for the progress of the Indonesian nation in the future, because there are many generations of the nation who marry underage and end up being young widows, it's no wonder the number of widows always increases every year, so that's where counseling about early marriage is needed as an effort to stop growth the number of widows in Lombok. The method used in this research is literature study by reading and recording and processing research materials sourced from books, journals, scientific articles, and online media. The author notes that there are several factors that influence early marriage, namely educational factors, cultural factors of elopement (merariq), family factors, psychological factors, and social environment. Of the several factors above, of course, counseling is very much needed, where the forms of counseling or counseling guidance that must be given are, namely family counseling, adolescent counseling, educational and religious counseling. Key Word: Counseling, Early Marriage, and Widows.